Konstruksi Penggemar Bangtan Boys dalam Komunitas Adorable Representative M.C. for Youth di Surabaya tentang Nasionalisme - Riski Darma Santi; Sarmini Sarmini (Universitas Negeri Surabaya (Unesa), 2023)
Adorable Representative M.C. for Youth (ARMY) Surabaya is a fan community for the K-Pop BTS group in Surabaya. In contrast to fan communities in general, in this community fans have an understanding of nationalism that is interesting to study. The research is examined by the social construction theory of Peter L. Berger and Thomas Luckmann to analyze the construction of nationalism and the dominant factors that influence it. This study uses a case study design with reference to the ideas put forward by Robert K. Yin. The subjects in this study were three BTS fans. The research location is in the city of Surabaya, precisely in the ARMY Surabaya community. Data collection techniques used were participant observation and in-depth interviews. Data found in the field were then analyzed using Miles and Huberman's model which is associated with social construction theory. The results of the study show that the construction of BTS fans in the ARMY Surabaya community about nationalism occurs in three moments. First, at the moment of internalization, fans get socialization both primary and secondary. Second, at the moment of objectification, fans have shared knowledge about nationalism through a process of habituation and institutionalization. Third, at the moment of externalization of the fans' construction of nationalism it is poured out in three forms, namely as communication that takes place in harmony, appreciation of national identity, and obedience to regulations. Of the three forms of construction, nationalism tends to be understood by fans as a harmonious communication and appreciation of national identity.